Evolution of mitochondrial RNA editing sites and stop codon-lacking transcripts in angiosperms - Runxian Yu; Lumei Liu; Matthias Jost; Ran Zhao; Stefan Wanke; Yuannian Jiao (Communications Biology)
Abstract While the evolution of mitochondrial protein-coding genes in angiosperms has been extensively studied, the post-transcriptional RNA processing remains under-explored. Leveraging newly generated and public RNA-seq data from twenty representative angiosperms, we systematically inferred the gain-and-loss dynamics of RNA editing sites within mitochondrial protein-coding genes. Our findings reveal magnoliids retain more ancestral RNA editing sites compared to monocots and eudicots. Furthermore, we uncovered contrasting correlations between gene expression levels and RNA editing density: negative in core mitochondrial genes but positive in variable genes. We also identified widespread occurrence of stop codon-lacking transcripts of four genes (ccmC, nad6, sdh3 and sdh4) across angiosperms, a phenomenon mainly reported in Arabidopsis thaliana. Besides the known t-element previously identified in A. thaliana, we revealed another distinct motif that may contribute to the post-transcriptional processing of nad6 transcripts. Novel stem-loop motifs that may mediate the formation of stop codon-lacking transcripts of ccmC, sdh3 and sdh4 genes were also identified. Collectively, our study sheds light on the ancestral RNA editing characteristics of angiosperm mitochondrial genes, and provides evidence that the processing-derived stop codon-lacking transcripts predate the divergence of angiosperms.